Golden calf traditions in early Judaism, Christianity, and Islam - Mason, Eric Farrel (Themes in Biblical Narrative, 2018)
The seventeen studies in Golden Calf Traditions in Early Judaism, Christianity, and Islam explore the biblical origins of the golden calf story in Exodus, Deuteronomy, and 1 Kings, as well as its reception in a variety of sources: Hebrew Scriptures (Hosea, Jeremiah, Psalms, Nehemiah), Second Temple Judaism (Animal Apocalypse, Pseudo-Philo, Philo, Josephus), rabbinic Judaism, the New Testament (Acts, Paul, Hebrews, Revelation) and early Christianity (among Greek, Latin, and Syriac writers), as well as the Qur'an and Islamic literature. Expert contributors explore how each ancient author engaged with the calf traditions-whether explicitly, implicitly, or by clearly and consciously avoiding them-and elucidate how the story was used both negatively and positively for didactic, allegorical, polemical, and even apologetic purposes.